The Bateman–Luke variational formalism in a sloshing with rotational flows - Timokha, A.N. (Доповіді НАН України, 2016)
Based on a presentation of the velocity field in terms of Clebsch potentials, the Bateman–Luke variational formalism is generalized for the sloshing of an ideal incompressible liquid with rotational flows.